Lithium Inhibits GSK3β and Augments GluN2A Receptor Expression in the Prefrontal Cortex - Monaco, Sarah A.; Ferguson, Brielle R.; Gao, Wen-Jun (Frontiers in Cellular Neuroscience, 2018)
Glycogen synthase kinase 3β (GSK3β) is a highly conserved serine/threonine kinase that has been implicated in both psychiatric and neurodegenerative diseases including schizophrenia, bipolar disorder, and Alzheimer’s disease; therefore regulating its activity has become an important strategy for treatment of cognitive impairments in these disorders. This study examines the effects of lithium on GSK3β and its interaction with β-catenin and NMDA receptors within the prefrontal cortex. Lithium, a clinically relevant drug commonly prescribed as a mood stabilizer for psychiatric disorders, significantly increased levels of phosphorylated GSK3β serine 9, an inhibitory phosphorylation site, and decreased β-catenin ser33/37/thr41 phosphorylation in vitro, indicating GSK3β inhibition and reduced β-catenin degradation. GluN2A subunit levels were concurrently increased following lithium treatment. Similar alterations were also demonstrated in vivo; lithium administration increased GSK3β serine 9 phosphorylation and GluN2A levels, suggesting a reduced GSK3β activity and augmented GluN2A expression. Correspondingly, we observed that the amplitudes of evoked GluN2A-mediated excitatory postsynaptic currents in mPFC pyramidal neurons were significantly increased following lithium administration. Our data suggest that GSK3β activity negatively regulates GluN2A expression, likely by mediating upstream β-catenin phosphorylation, in prefrontal cortical neurons. Furthermore, our biochemical and electrophysiological experiments demonstrate that lithium mediates a specific increase in GluN2A subunit expression, ultimately augmenting GluN2A-mediated currents in the prefrontal cortex.